Personality stability and change across the academic semester - Stephanie M. Anglin; Rachel S. Rubinstein; Dustin A. Haraden; Caitlin Drummond Otten; Brandon Mangracina; K. Mackenzie Shaw (Frontiers in Psychology, 2025)
This study tested competing hypotheses of student personality change across the academic semester, and examined the academic, social, extracurricular, health, and affective experiences associated with changes. Previous research suggests that personality can vary substantially in response to situational factors (Situational Perspective) but shows high levels of consistency over time (Personality Stability). Despite consistency, research also finds developmental patterns of change, particularly in transitional periods such as college as young adults adapt to social role changes (Maturity Principle). We asked college students to complete measures of personality and experiences at the beginning and two-thirds of the way through the Fall semester. The Situational Perspective predicts that personality will change in response to changes across the semester (e.g., in workload), with conscientiousness and extraversion decreasing and neuroticism increasing, while the Maturity Principle predicts that conscientiousness and agreeableness will increase and neuroticism will decrease as students adapt to new roles and expectations, and the Personality Stability Perspective predicts that personality will remain unchanged. We found a decrease in conscientiousness, consistent with the Situational Perspective, along with decreases in agreeableness and openness, which were unpredicted from all three theories. Changes in personality co-occurred with declines in subjective wellbeing, social support, and health behaviors. Our results extend prior research observing personality changes associated with maturity over the college years, finding short-term declines in traits associated with maturity over the semester. Although further research is needed, these findings may suggest that college students must face and adapt to new challenges and expectations before growing from their experiences.